Tailoring the Optical and Electrical Properties of ZnO Films: Co-Doping with F and In - Ibrahim Gunes (Gazi Üniversitesi Fen Bilimleri Dergisi)
In this study, undoped ZnO, 3% In doped ZnO and 5% F: 3% In co-doped ZnO films were successfully synthesized via ultrasonic spray pyrolysis. The study objective is to investigate the changes in physical properties especially opto-electrical of ZnO films with F:In co-doping strategy and thus contribute to developing high-performance materials for opto-electronic devices. Structural analysis showed that obvious changes occurred in the ZnO crystal structure with doping and the dopant atoms were successfully integrated into the ZnO lattice. Morphological studies showed that 5% F: 3% In co-doped ZnO films exhibit a homogeneous, nanostructured, and compact surface, with surface roughness being lower than undoped ZnO films. Moreover, SEM images identified granular nanostructures in 3% In doped and 5% F: 3% In co-doped ZnO films, which were attributed to the stabilization of grain boundaries by dopant atoms, promoting a uniform structure. Optical analysis revealed that the 5% F: 3% In co-doped ZnO film exhibited a transmittance of 83% in the visible region and a wider optical band gap of 3.32 eV compared to other films. Electrical characterization demonstrated that the carrier concentration of ZnO films was 1.031017 cm-3, increasing markedly to 1.141018 cm-3 in 5% F: 3% In co-doped ZnO film. Additionally, the resistivity of the 5% F: 3% In co-doped ZnO film was detected at the lowest level of 1.6510-1 cm. This data reveals the potential of 5% F: 3% In co-doped ZnO films for advanced opto-electronic applications, including photovoltaic cells, display technologies, and LEDs. Co-doping ZnO films with fluorine and indium emerge as a promising strategy to enhance electrical and optical properties.